Draft Annual Plan, 2003-04 Volume I (Part-I) Government of Uttar Pradesh - Planning Commission (Planning Commission, 2003)
Poverty levels in Uttar Pradesh have gone down steadily since the early seventies, but still continue to be much higher than in most of the other states with a few exceptions like Bihar and Orissa. The number of persons below poverty line in 1973-74 was 535.73 lakh, comprising 57.07% of State's population and 16.7% of the number of persons below poverty line in the country. The only States with still higher percentages were Orissa (66.2%), West Bengal (63.4%), Bihar (61.9%), Madhya Pradesh (61.8%) and Kerala (59.8). The State with lowest percentage (28.2) was Punjab . By the year 1983, the percentage of population below poverty line came down to 47.07%, though the number of poor increased to 556.74 lakh. Poverty ratio further declined to 41.46 % in 1987-88. The situation remained almost unchanged between 1887-88 and 1993-94, with the percentage of population below poverty line showing a marginal decline to 40.85%.
Draft Annual Plan, 2003-04 Volume I (Part-I)
Government of Uttar Pradesh